2012
DOI: 10.1111/j.1743-7563.2012.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the cancer journey: A review of patient navigator programs for Indigenous cancer patients

Abstract: Patient navigator programs have evolved to facilitate access to care and improve outcomes for Indigenous cancer patients. We reviewed the scientific literature on patient navigator programs in Indigenous people with cancer. We conducted a review of the published literature up to 13 April 2011. PubMed, MEDLINE and CINAHL databases were searched for original articles on Indigenous patient navigation programs. The review produced eight relevant articles covering two specific programs, the Native Sisters Program a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Potential reasons for these delays likely include factors relating to timely access to appropriate health care and patientrelated factors such as fear and cultural beliefs, as well as interactions between them (Javid et al, 2014;Kolahdooz et al, 2014;Roder et al, 2012;Whop et al, 2012). Potential reasons for these delays likely include factors relating to timely access to appropriate health care and patientrelated factors such as fear and cultural beliefs, as well as interactions between them (Javid et al, 2014;Kolahdooz et al, 2014;Roder et al, 2012;Whop et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential reasons for these delays likely include factors relating to timely access to appropriate health care and patientrelated factors such as fear and cultural beliefs, as well as interactions between them (Javid et al, 2014;Kolahdooz et al, 2014;Roder et al, 2012;Whop et al, 2012). Potential reasons for these delays likely include factors relating to timely access to appropriate health care and patientrelated factors such as fear and cultural beliefs, as well as interactions between them (Javid et al, 2014;Kolahdooz et al, 2014;Roder et al, 2012;Whop et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additional approaches include cancer education programmes which support the role of Indigenous Health Workers(Le et al, 2013;Murphy et al, 2015;Smith, 2012;Whop et al, 2012;Zorbas & Elston, 2016), a key source of cancer information, health promotion and support for Indigenous patients undergoing cancer treatment(Bernardes et al, 2012).While the review found consistent evidence for variations in breast cancer survival, studies reporting other outcomes were limited. Additional approaches include cancer education programmes which support the role of Indigenous Health Workers(Le et al, 2013;Murphy et al, 2015;Smith, 2012;Whop et al, 2012;Zorbas & Elston, 2016), a key source of cancer information, health promotion and support for Indigenous patients undergoing cancer treatment(Bernardes et al, 2012).While the review found consistent evidence for variations in breast cancer survival, studies reporting other outcomes were limited.…”
mentioning
confidence: 99%
“…will still be more likely to be subjected to longer delays. Improved patient navigation through cancer care coordinators (CCC) has been shown to help reduce delays, especially for women who are at-risk for longer delays which include women of minority ethnicity and low socioeconomic groups [38]. The Waikato District Health Board has two full-time CCC’s providing support for women with breast cancer since 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Across the cancer care continuum, PS has emerged as an important strategy to address many barriers to cancer prevention [28], early detection [29,30], treatment [22,31], and survivorship [31,22]. Peer supporters often work with patients and/or health care providers to address system-level barriers, such as fragmented care, financial constraints, other practical challenges (e.g., transportation, employment concerns, child care), and communication difficulties [32,25].…”
Section: Introductionmentioning
confidence: 99%